Торцовый коллектор электрической машины - Багров Г. Н. Георгий Николаевич; Бекишев Р. Ф. Рудольф Фридрихович; Качин С. И. Сергей Ильич; Константинов Г. Г. Геннадий Григорьевич; Лебедев С. И. Сергей Иванович
опубл. 15.08.82